Ancient Understanding of Time and the Background of Contemporary Historicism - D. G. Gorin (Концепт: философия, религия, культура, 2023)
Contemporary changes in historical culture associated with various states of modernity actualize the problem of the foundations and prerequisites of historicism as a principle of thinking characteristic of modern societies. The ancient historicism background consists primarily in the advanced concepts of time and eternity, which contain the potential variability in the understanding of historicity in modern philosophy and culture. At the same time, the problem of the historical variability of the world remained on the periphery of ancient philosophy and culture, and classical historicism, which was established in the second half of the 18th century, was based on the rejection of some aspects of the ancient heritage. In opposing being and becoming, ancient philosophy preferred being, which was also manifested in the preference for truth over time, for one over multiple. Classical historicism of modern times is focused on the idea of becoming, which in a new way reveals the contradictions between truth and time, one and multiple. Relativism and plurality are becoming features of modern transformations of historicism, in which the structures of time are preserved, dating back to the ancient concepts of chronos, kairos, eon, etc. Of particular interest are modern ideas about time, which go back to the ancient concept of objectified chronological time and its correlation with other forms of time conceptualization. In the historical consciousness of modern times, the ancient concepts of time were transformed under the influence of the prophetic sense of time, characteristic of the biblical tradition, in which the historical process is considered in the context of the gradual revelation of the original intention and meaning of history.